Performance Study of CuO/Cu4O3@C Composites in Electrocatalytic Reduction of CO2 - ZHANG Jinnan; GUO Tianyu; QI Yu; WANG Hongtao (Taiyuan Ligong Daxue xuebao)
[Purposes] Electrochemical CO2 reduction reaction (CO2RR) to high-value chemicals is currently receiving widespread attention. In order to improve the electrocatalytic activity and selectivity, it is necessary to prepare catalysts with superior CO2RR properties. [Methods] In this study, wheat bran-based biochar (C) was prepared and coupled with copper oxide to get composite electrocatalysts through a simple hydrothermal method, and physicochemical characterizations and electrochemical performance testings were further condueted. [Findings] The results suggest that the CuO/Cu4O3@C-2 shows the best Faradaic efficiency of C2H4 (46.32%) at -1.08 V (vs. RHE). Meanwhile, the sample displays excellent stability for 11.5 h at -1.08 V (vs. RHE). [Conclusions] This study provides a feasible strategy for the synthesis of cost-effective catalysts with high electrochemical performance.